Team Relationships and Performance: Evidence from Healthcare Referral Networks - Agha, Leila; Ericson, Keith Marzilli; Geissler, Kimberley H.; Rebitzer, James B. (Management Science, 2022)
We examine the teams that emerge when a primary care physician (PCP) refers patients to specialists. When PCPs concentrate their specialist referrals-for instance, by sending their cardiology patients to fewer distinct cardiologists-repeat interactions between PCPs and specialists are encouraged. Repeated interactions provide more opportunities and incentives to develop productive team relationships. Using data from the Massachusetts All Payer Claims Database, we construct a new measure of PCP team referral concentration and document that it varies widely across PCPs, even among PCPs in the same organization. Chronically ill patients treated by PCPs with a one standard deviation higher team referral concentration have 4% lower health care utilization on average, with no discernible reduction in quality. We corroborate this finding using a national sample of Medicare claims and show that it holds under various identification strategies that account for observed and unobserved patient and physician characteristics. The results suggest that repeated PCP-specialist interactions improve team performance.